Family Members’ Satisfaction Levels: Impact of An Intensive Care Unit Information Leaflet with Verbal Information Compared to Conventional Verbal Information - T Kumaravadivel Dharmalingam; Narendran Kunasakaran; Norazian Ahmad Zainuddin; Rajesh Kumar Muniandy (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2021)
Patients admitted to the Intensive Care Unit (ICU) experience intense physical stress. Family members of these patients also experience stress during the admission. Therefore, it is an important task of the ICU staff to provide the family members with appropriate and clear information. There are many methods to do this. This study aimed to compare the impact of two methods of information sharing on the satisfaction levels among families of ICU patients. The novel method being introduced and investigated was a locally designed information leaflet in combination with verbal explanation. This new method was compared with the traditional method of verbal explanation only. This was a randomized controlled study, conducted at the ICU of Teluk Intan Hospital. A total of 60 participants were enrolled, with 30 participants each in the intervention and control group. The Malay version of the Validated Critical Care Family Satisfaction Survey (CCFSS) was used to measure family satisfaction with the care received during their ICU admission. The intervention group reported significantly higher level of satisfaction in all of the components (Assurance, Proximity, Information, Support and Comfort). Upon further examination of the results of the intervention group, the scores in the Assurance, Proximity and Comfort component were significantly higher compared to the scores in the Information and Support component. Integrating an information leaflet with the traditional verbal method of delivering information has proven to provide a significant difference in satisfaction levels to the family members of patients who were admitted to the ICU.